Pathology of the Inventive Step Requirement in the Patent Law with a Look at Iranian Law - Najafi, Hamed (Frontiers in Law, 2023)
The of the inventive step requirement, which apparently guarantees the growth of innovation and pursues industrial and economic development, despite enjoying some benefits, has always faced challenges, and in some cases such challenges are in conflict with the basis of the patent system, and it shows that the patent system is not always socially useful. The analysis of the mentioned challenges is mainly based on the economic principles and assessment tools of the requirement, i.e., examiners and person having ordinary skill in the art. Iran’s patent system can also be criticized in terms of legislation and implementation and needs to be reformed. In this article, we intend to first examine the economic pathology regarding the assessment of the inventive step requirement in the patent system, then present the appropriate criterion that is similar to the copyright system, and explain the necessary suggestions.